The chance - Kingsbury, Karen (New York : Howard Books, 2013)
Vowing to meet eleven years after sealing letters they wrote to each other in an old metal box, best friends Ellie and Nolan both have reservations about seeing each other again as loneliness, personal tragedies, and a lack of faith haunt both of them.
Includes excerpt from the author's upcoming novel, Fifteen minutes.
Keywords: Man-woman relationships -- Fiction; Friendship -- Fiction; Faith -- Fiction; Love stories; Christian fiction